A Novel Homozygous Frameshift WDR81 Mutation associated with Microlissencephaly, Corpus Callosum Agenesis, and Pontocerebellar Hypoplasia - Kalmár, Tibor; Szakszon, Katalin; Maróti, Zoltán; Zimmermann, Alíz; Máté, Adrienn; Zombor, Melinda; Bereczki, Csaba; Sztriha, László (Journal of Pediatric Genetics, 2020)
Microlissencephaly is a brain malformation characterized by microcephaly and extremely simplified gyral pattern. It may be associated with corpus callosum agenesis and pontocerebellar hypoplasia. In this case report, we described two siblings, a boy and a girl, with this complex brain malformation and lack of any development. In the girl, exome sequencing of a gene set representing 4,813 genes revealed a homozygous AG deletion in exon 7 of the WDR81 gene, leading to a frameshift (c.4668_4669delAG, p.Gly1557AspfsTer16). The parents were heterozygous for this mutation. The boy died without proper genetic testing. Our findings expand the phenotypic and genotypic spectrum of WDR81 gene mutations.
Keywords: microlissencephaly; pontocerebellar hypoplasia; WDR81 mutation